ROLE OF PUBLIC CONTROL IN THE ACTIVITIES OF REPRESENTATIVE AUTHORITIES IN THE LOCATIONS - Makhsad ISABAEV (Scholar Express Journals, 2022)
The article highlights the importance of citizen participation in local government through public participation, and explores the need for openness and transparency in this process
Keywords: Cooperation; Participation; Transparency